Variation in the Exine Ornamentation Patterns in Taro (Colocasia esculenta (L.) Schott.) with respect to Geographical Distribution - Beevi, P. Nusaifa; Sreekumari, M.T. (JOURNAL OF ROOT CROPS, 2013)
Light microscopic (LM) and scanning electron microscopic (SEM) observations were carried out in taro (Colocasia esculenta) pollen grains for detecting intra-specific variability as reflected in pollen features at Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala, India. The pollen grains were found to occur in monads and were inaperturate. Pollen diameter was found to be below 25Î¼m and the shape was globular or spheroidal. Despite the uniformity in aperture type, pollen shape and size, wide intraspecific variations were observed with regard to the exine sculpturing. The echinate excrescence characteristic of the family Araceae was observed in all the accessions studied. The exine surface showed tilate (tile shaped) appearance with the arrangements of basal plates holding the column and wide variations were observed in the size, shape, arrangement and pattern of these basal plates. Based on these features five basic types of exine ornamentation pattern were observed in taro. The variations observed in the exine ornamentation pattern were correlated with the geographical distribution of the plants under study